Educação Rural no Município de Francisco Beltrão entre 1948 a 1981: a escola multisseriada - Cattelan, Carla (2014)
This research had as study object the multigrade rural schools which were built and implemented between the years 1948 and 1981 in Francisco Beltrão city. From this object I raise the following issues: How multigrade rural schools were established and held first in Vila Marrecas, and later in Francisco Beltrão, between the years 1948 and 1981? The objective has consisted in analyzing de educational historical construction that allowed the structuring of multigrade rural schools, including the challenges in the pedagogical and administrative issues articulated to social, economic, political, historical and cultural aspects that underpinned this process. The aim was delimited as beginning the year 1948 to be the year in which it has records of construction of first school, funded and sustained by the National Agricultural Colony General Osório (CANGO), a federal agency. And for being the year of installation of the seat of CANGO in Vila Marrecas Francisco Beltrão. The final cut was the year 1981, by the issuance of Executive Decree n°365, through which was ratified by the creation acts of schools in the rural zone, created so far and that were active. The intention was to rescue the historical forms of rural education, the established schools in the communities, creating a relation with the educational policy and with de changes of country life, supported by the dialectical historical materialism, to understand the historical process of multigrade rural school, I use the analysis of documentary sources, oral testimonials, photographs, newspaper clippings, journals and bibliographies about the region. The resulting analysis of this study highlighted the interest of the federal agency as the effectiveness of rural primary education and the service to existing population demand between 1940 and 1950. With the rise to municipality, Francisco Beltrão, from 1952, it incorporated together with the aid of communities, the construction and grocery of rural schools, which contributed significantly to education of all children of rural zone.